2016
DOI: 10.1111/ejss.12330
|View full text |Cite
|
Sign up to set email alerts
|

Application of X‐ray tomography to quantify macropore characteristics of loess soil under two perennial plants

Abstract: SummaryWith the advent of large-scale restoration of vegetation in the Loess Plateau, northwest China, there has been an increase in concern about the suitability of loess soil to support permanent vegetation cover. The quantification of soil macropore characteristics could be critical in determining the architecture and hydrological processes of loess soil on the plateau. In this research, we compared the effects of Purple alfalfa (Medicago sativa L.) and Korshinsk peashrub (Caragana korshinskii K.) on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…For example, studies have been widely carried out on segmentation of X‐ray CT images (Baveye et al, ; Iassonov, Gebrenegus, & Tuller, ; Schlüter, Sheppard, Brown, & Wildenschild, ) involving image resolution selection (Sleutel et al, ; Wildenschild et al, ), representative elementary area identification (San José Martínez, Caniego, García‐Gutiérrez, & Espejo, ), and optimal thresholding methods (Elliot & Heck, ; Smet, Plougonven, Leonard, Degré, & Beckers, ; Wang, Kravchenko, Smucker, & Rivers, ); quantification and reconstruction of the pore structure (Marcelino, Cnudde, Vansteelandt, & Carò, ) such as characterization of macropores (Garbout, Munkholm, & Hansen, ; Luo, Lin, & Schmidt, ), extraction of three‐dimensional (3D) typical pore parameters (Al‐Raoush & Willson, ; Luo, Lin, & Li, ), and assessing the spatial variability of soil structure (Carducci, Zinn, Rossoni, Heck, & Oliveira, ); as well as the relationship between pore characteristics and soil functions (Helliwell et al, ) including correlations with soil physical properties (Anderson, Gantzer, Boone, & Tully, ; Munkholm, Heck, & Deen, ) and explanation of the hydraulic conductivity (Luo, Lin, & Halleck, ; Naveed et al, ; Paradelo et al, ; Tracy et al, ). Although the majority of current case studies focus on naturally cultivated soils, there are still some reports confirming that images extracted from X‐ray CT are effective in quantifying pore characteristics of unnaturally soils such as reconstructed, degraded, and reclaimed soils (Dowuona, Taina, & Heck, ; Langmaack, Schrader, Rapp‐Bernhardt, & Kotzke, ; Li, Shao, & Jia, ; Wang, Guo, Bai, & Yang, ). Langmaack et al () reported an interesting case performing X‐ray CT method to study the soil structure rehabilitation of degraded soil caused by compaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have been widely carried out on segmentation of X‐ray CT images (Baveye et al, ; Iassonov, Gebrenegus, & Tuller, ; Schlüter, Sheppard, Brown, & Wildenschild, ) involving image resolution selection (Sleutel et al, ; Wildenschild et al, ), representative elementary area identification (San José Martínez, Caniego, García‐Gutiérrez, & Espejo, ), and optimal thresholding methods (Elliot & Heck, ; Smet, Plougonven, Leonard, Degré, & Beckers, ; Wang, Kravchenko, Smucker, & Rivers, ); quantification and reconstruction of the pore structure (Marcelino, Cnudde, Vansteelandt, & Carò, ) such as characterization of macropores (Garbout, Munkholm, & Hansen, ; Luo, Lin, & Schmidt, ), extraction of three‐dimensional (3D) typical pore parameters (Al‐Raoush & Willson, ; Luo, Lin, & Li, ), and assessing the spatial variability of soil structure (Carducci, Zinn, Rossoni, Heck, & Oliveira, ); as well as the relationship between pore characteristics and soil functions (Helliwell et al, ) including correlations with soil physical properties (Anderson, Gantzer, Boone, & Tully, ; Munkholm, Heck, & Deen, ) and explanation of the hydraulic conductivity (Luo, Lin, & Halleck, ; Naveed et al, ; Paradelo et al, ; Tracy et al, ). Although the majority of current case studies focus on naturally cultivated soils, there are still some reports confirming that images extracted from X‐ray CT are effective in quantifying pore characteristics of unnaturally soils such as reconstructed, degraded, and reclaimed soils (Dowuona, Taina, & Heck, ; Langmaack, Schrader, Rapp‐Bernhardt, & Kotzke, ; Li, Shao, & Jia, ; Wang, Guo, Bai, & Yang, ). Langmaack et al () reported an interesting case performing X‐ray CT method to study the soil structure rehabilitation of degraded soil caused by compaction.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al () was successful in quantifying the pore distribution of reconstructed soils using X‐ray CT images. Li et al () indicated that it was feasible to apply X‐ray CT images to characterize the macropore of loess soil reclaimed by vegetation. So far, however, research on sodic soils is largely insufficient, very few typical findings have been reported on quantification of pore characteristic of sodic soils (Yu, Yang, Lin, Ren, & He, ), especially for their 3D pore characteristics before and after reclamation.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray computed tomography (CT) is an imaging technique based on the computation of many transmission measurements of photographs [ 26 ]. CT has been used to determine the shape, size, orientation, and size distribution of pores at high resolutions [ 27 ]. Kumar et al [ 28 ] quantified soil pore features, including the number of pores, number of macropores, number of coarse mesopores, porosity, macroporosity, coarse mesoporosity and fractal dimension, in agroforestry and grass buffer areas using X-ray CT. Meng et al [ 23 ] quantified soil macropore networks under different forest communities using industrial CT in a mountainous area.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters can be broken down into two major categories: (1) Parameters that describe the reaction space (i.e., the 3D pore space itself) and (2) parameters that describe the complexity or connectivity of the pore network (i.e., the number of pore connections per unit volume). Variables that belong to the first category are: Visible porosity [15,64,[70][71][72][73], pore size distribution [50,70,73,74], pore surface area [75][76][77], pore thickness (i.e., diameter) [71,77,78], and total visible pore volume [42,50,79]. Variables that fall in the second category rely largely on what is referred to as the skeleton, or single voxel width medial axes, of the pore network [47,80].…”
Section: Pore Network Metrics Have Differential Power To Explain Avaimentioning
confidence: 99%